Spectrum and outcome of gastric outlet obstruction in a tertiary care hospital - V., Sachin; R. S., Ravya; V., Sunil Kumar (International Surgery Journal, 2018)
Background: Gastric Outlet Obstruction is a disorder wherein there is an obstruction in the opening of the stomach (Pylorus), blocking the entrance of ingested food coming from the stomach to the duodenum. Gastric Outlet Obstruction is the one of the most common clinical scenarios encountered in general surgery. Pyloric obstruction occurs in 2-4% of patients with chronic duodenal ulcer and it is described by Sir James Walton as “the stomach you can hear, the stomach you can feel and the stomach you can see”. Predominant cause for Gastric Outlet Obstruction has changed substantially with identification of H. Pylori and the use of proton pump inhibitor. In this study the various aspects and management of Gastric Outlet Obstruction are analysed. Methods: This prospective cohort study of 18 months duration was conducted among 50 patients in the department of general surgery from August 2016 to February 2018. The study population included patients presenting with gastric outlet obstruction in the deparment of general surgery who are treated on in-patient basis. An elaborate study of these cases was done and data pertaining to history, clinical features, investigations, management and follow up collected in a structured proforma. Results: Of the 50 cases of gastric outlet obstruction, 30 patients were diagnosed carcinoma pylorus and 17 of them were found to have cicatrising ulcer. Remaining 3 patients had other causes attributed to the presentation. The age incidence of the patients in this study ranged from 20 to 70 years with a mean age of 45.2 years. Majority of patients were manual labourers. 70% of the study subjects were smokers and 60% consumes alcohol. Vomiting and abdominal pain were the predominant symptom with recorded loss of weight in 35 cases. Conclusions: Gastric outlet obstruction is a common presentation of malignancy and cicactrising duodenal ulcers. However there has been changing trends in the pattern of disease incidence in view of changing trends in management and investigation modalities.